Temporal distribution and composition of the ichthyoplankton from Leopoldo's Inlet on the Upper Parana River floodplain (Brazil) - de Castro, R. J.; Nakatani, K.; Bialetzki, A.; Sanches, P. V.; Baumgartner, G. (Cambridge University Press, 2002)
Temporal distribution and composition of ichthyoplankton and their relationships with some environmental variables of Leopoldo's Inlet (Ressaco do Leopoldo) on the upper Parana River floodplain, southern Brazil, were analysed. Samples were taken from February 1991 to February 1992, and 3480 larvae were collected. The highest density of larvae was observed in November 1991 (36.79 larvae/ 10 m(3)) at night (night/day ratio 7: 1). Species composition showed a predominance of Characiformes (80%). There was a high density (4.28 larvae/10 m(3)) of Bryconamericus stramineus throughout almost the whole study period, the majority of the species were more frequently collected at night. Pearson's correlation indicated a relationship between larval density, temperature, and pluviometric index. Leopoldo's Inlet, whose ichthyofauna is mainly composed of grazing and resident species. shows favourable conditions for fish reproduction and development.
Keywords: temporal distribution; ichthyoplankton; floodplain; Parana River